Planificación energética para el ahorro de fueloil en una lavandería industrial (2018)
In this paper was applied a method of energy planning, compatible with ISO 50001 standard, in an industrial laundry. In the analysis, three input variables were considered: level of production, technical condition of the system and operating regime. The past, present and future of fuel oil consumption in the steam generation and use was examined, establishing the causes of deterioration of consumption indicator. A study of load and capacity in the system identified potential savings through improved operating regime. A new regime for the operation of boilers was proposed and implemented, saving 16% of fuel. With the results of these measurements, the baseline was developed and goals are established.